2022
DOI: 10.1002/bse.3286
|View full text |Cite
|
Sign up to set email alerts
|

Activating the different sides of top management team faultlines in enterprise sustainable development: Is environmental responsibility a burden or boost to small and medium‐sized enterprises in China?

Abstract: Whether environmental responsibility can promote corporate performance has always been a focus of debate in theory and practice. We address the dispute regarding the effect of environmental responsibility by focusing on small and medium‐sized enterprises (SMEs) in China. Furthermore, based on team faultline theory, we argue that top management team (TMT) faultlines and bankruptcy threat combine to affect the relationship between environmental responsibility and long‐term performance in SMEs. Using data from 41… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 135 publications
0
5
0
Order By: Relevance
“…The main reason for this result may be the lack of activation of faultlines, particularly in the case of product‐unrelated service transition (Liu & Van Peteghem, 2022 ). Notably, resource actions in this context can benefit from cognitive diversity and information advantages (Elmagrhi et al, 2019; Chen et al, 2022 ). The negligible moderating effect and opposing result warrant further discussion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The main reason for this result may be the lack of activation of faultlines, particularly in the case of product‐unrelated service transition (Liu & Van Peteghem, 2022 ). Notably, resource actions in this context can benefit from cognitive diversity and information advantages (Elmagrhi et al, 2019; Chen et al, 2022 ). The negligible moderating effect and opposing result warrant further discussion.…”
Section: Discussionmentioning
confidence: 99%
“…Following the resource orchestration perspective, Ndofor et al ( 2015 ) argue that TMT faultlines can affect both the conversion of resources to actions and the conversion of actions to performance. Similarly, Chen et al ( 2022 ) suggest that TMT faultlines influence the ability to integrate resources into environmental responsibility decision processes. Moreover, existing studies have confirmed the significant role of TMT faultlines in facilitating green technology innovation (Ma et al, 2021 ).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…A business's bankruptcy has significant consequences for many parties, including clients, vendors, creditors, and employees [ 3 ]. At the same time, small and medium-sized enterprises (hereafter, SMEs) play a vital role in the country's economic development [ 4 ]. They contribute to the employment generation [ 5 , 6 ], innovation [ 7 ], and overall growth of the economy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%